Synthesis of Butyric Acid Nitrification Derivatives and Adiabatic Thermal Analysis of Reaction With Nitric Acid - Shi-ming FENG; Qian-hong GAO; Xiao-long ZHONG; Shuang-ling TANG (He huaxue yu fangshe huaxue)
Tributyl phosphate(TBP) undergoes stepwise degradation in the post-treatment system to produce butanol, which is ultimately converted into butyric acid. Butyric acid can gradually accumulate in the system and undergo nitration reactions triggered by free radicals such as \begin{document}${ · OH} $\end{document} to produce nitration derivatives. The formation of “red oil” during the post-treatment process is inseparable from the production of nitro compounds. In this work, tert-butyl acrylate and nitromethane were used as raw materials to obtain the typical nitration product of butyric acid, 4-nitrobutyric acid(hereinafter referred to as nitrobutyric acid), through synthetic methods. Its structural formula is (CH2NO2)(CH2)2COOH. The synthesized sample was structurally analyzed using infrared spectroscopy and nuclear magnetic resonance spectroscopy. The exothermic behavior of nitrobutyric acid and nitric acid was explored using an adiabatic accelerating calorimeter. Comparative analysis was conducted by varying the molar ratio(r) of nitrobutyric acid to nitric acid and nitric acid concentration. The THI index method is used to assess the risk of the system. The results indicate that the infrared spectrum of the synthesized sample bears carboxyl and nitro groups, and the structure shown in the nuclear magnetic resonance spectrum corresponds to the target product. Under adiabatic conditions, pure nitrobutyric acid undergoes self oxidation heat release within the set temperature range, and the heat release process first accelerates and then slows down; the starting temperature of the self exothermic process of the sample is 90.4 ℃, and the ending temperature is 153.6 ℃. The adiabatic temperature rise during the self exothermic process is 63.2 ℃, and the reaction heat reaches 1485.65 J/g. At 126.5 ℃, the temperature rise rate reaches the maximum value of 1.7 ℃/min, and the maximum pressure rise rate is 0.1 bar/min(1 bar=100 kPa). After adding nitric acid, the initial exothermic temperature decreases to around 75.6 ℃. As the molar ratio of nitrobutyric acid to nitric acid increases, the termination exothermic temperature and adiabatic temperature rise show an overall increasing trend, while the reaction heat decreases with increasing sample mass. The increase in nitric acid concentration gradually intensifies the reaction process of the system. The highest exothermic temperature, maximum temperature rise rate, and heat release rate of the sample all show an upward trend. When the nitric acid concentration is 10.0 mol/L, the maximum temperature rise rate reaches 457.9 ℃/min, the maximum pressure rise rate can reach 76.1 bar/min, and the adiabatic temperature rise reaches 130.5 ℃. According to the thermal risk assessment results, the THI values of samples with different molar ratios of nitrobutyric acid to nitric acid system are generally above 0.3, which is at a high risk level. The system samples are also generally at a high risk level under different nitric acid concentrations, and the THI values of the samples increase with the increase of nitric acid concentration, indicating that the increase of nitric acid concentration will make the reaction more intense and increase the risk.